Threat of Sexual Abuse Among in-School Adolescents in Kwara State - Abdulkareem; Olalekan Abubakar; Kamoru Abidoye Tiamiyu; Akeem Omowumi Raheem; Habibat Bolanle Abdulkareem; Garba Bilikis (Formosa Journal of Multidisciplinary Research, 2023)
This paper reviewed on sexual abuse among adolescents to uncover areas that would lead to further researches and proffer a lasting solution. Sexual abuse of minors is an offense that is widely denounced. There exist various elements or causes of child sexual violence that the general public is unaware of. In order to safeguard children in society, it is critical to comprehend these variables. Sexual abuse has highly serious aftereffects that have a reflective impact on the victims' physical and mental health. The abuse upsets the child's bodily and mental order, the aftereffects are excruciating. Victims experience lifelong physical health issues as well as severe stress. It is therefore suggested that parents and guardians should watch their wards closely.